Pelatihan Pembuatan Lilin Abadi sebagai Upaya Peningkatan Keterampilan dan Kemandirian Ekonomi Masyarakat - Ifnu Wisma Dwi Prastya (Nawasena Bhakti, 2026)
The economic problems of rural communities and the low utilization of household waste into economically valuable products remain challenges in efforts to improve community welfare. Used cooking oil waste, which is generally discarded directly, has the potential to cause environmental pollution if not managed properly. This community service activity aims to enhance the skills and economic independence of the community through training in making eternal candles in Gunungrejo Village, Kedungpring District, Lamongan Regency. The method of implementing the activities was carried out through several stages, namely preparation, socialization, practical training, evaluation, and follow-up community assistance. The training was conducted on December 24, 2024, using a hands-on method for processing used cooking oil into eternal candles that have utility and market value. The results of the activities showed an increase in the knowledge and skills of the community in utilizing household waste into creative products, as well as the emergence of motivation to develop home-based businesses centered on eternal candles. This activity has a positive impact on increasing environmental awareness, productive skills, and opportunities for sustainable economic independence of the community.